Odpowiedzi

Najlepsza Odpowiedź!
2010-02-05T17:52:40+01:00
Z1=-2+3i , z2=-1-2i
z1+z2= -2+3i-1-2i=-3+i

z1*z2=(-2+3i)(-1-2i)=2+4i-3i-(3i)(2i)=2+i+6=8+i (należy pamiętać, że i²=-1)
2010-02-05T17:56:57+01:00
-2+3i-1-2i=-3+i
(-2+3i)(-1-2i)=2+4i-3i+6=8+i
  • Roma
  • Community Manager
2010-02-05T18:07:53+01:00
Z₁ = -2 + 3i
z₂ = -1 - 2i

z₁ + z₂ = (-2 + 3i) + (-1 - 2i) = (-2 - 1) + (3 - 2)i = -3 + i

z₁ × z₂ = (-2 + 3i) × (-1 -2i) = -2×(-1) + (-2)×(-2)i + 3i×(-1) + 3i×(-2)i = 2 + 4i - 3i + (-6×i²) = 2 - i + (-6)×(-1) = 2 - i + 6 = 8 + i